2020
DOI: 10.1038/s41419-020-2426-z
|View full text |Cite
|
Sign up to set email alerts
|

MSC-induced lncRNA HCP5 drove fatty acid oxidation through miR-3619-5p/AMPK/PGC1α/CEBPB axis to promote stemness and chemo-resistance of gastric cancer

Abstract: Chemotherapy is the first-tier treatment regime for gastric cancer (GC) patients at advance stages. Mesenchymal stem cell (MSC) cam affect drug-resistance of GC cells in tumor microenvironment, but the detailed mechanism remains poorly understood. Present study aimed to investigate the regulation of MSC-induced long non-coding RNA (lncRNA) in GC. Dysregulated lncRNAs in GC were analyzed based on GEO data. Stemness and drug-resistance of GC cells were detected by sphere formation, colony formation, CCK-8, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 61 publications
(100 reference statements)
0
118
0
1
Order By: Relevance
“…Therefore, the call for investigation in the mechanisms underlying the onset and progression of GC is pressing. 4 Endogenous RNAs as they are, microRNAs (miRNAs) can reversely regulate approximately 30% of human genes through binding to the complementary 3 'untranslated region (3ʹ-UTR). 5 According to reports, the role of miRNAs varies in different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the call for investigation in the mechanisms underlying the onset and progression of GC is pressing. 4 Endogenous RNAs as they are, microRNAs (miRNAs) can reversely regulate approximately 30% of human genes through binding to the complementary 3 'untranslated region (3ʹ-UTR). 5 According to reports, the role of miRNAs varies in different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated the critical modulating role of lncRNAs in tumor stemness phenotype as well as chemosensitivity (26,27). In the current study, we for the rst time systematically explored the potential signi cance of LINC00680 in HCC stemness properties and sensitivity to conventional HCC chemotherapeutic drugs, such as 5-Fu.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a large number of studies have shown that, in addition to mRNAs, non-coding RNAs also related to drug resistance of cancers, including gastric cancer [33], bladder cancer [34], lung adenocarcinoma [35]. Moreover, in CRC drug resistance studies, it was reported that LINC00957 could increase 5uorouracil resistance and result in poor survival of patients [36], hsa_circ_0079662 was related to oxaliplatin resistance via TNF-α pathway [25], microRNA-375-3p was involved in 5-uorouracil resistance by targeting thymidylate synthase [37].…”
Section: Discussionmentioning
confidence: 99%